1999
DOI: 10.1183/09031936.99.14510289
|View full text |Cite
|
Sign up to set email alerts
|

Do hormonal contraceptives influence asthma severity?

Abstract: There is some evidence that endogenous progesterone and oestrogen levels influence asthma severity in females, but little is known about the effects of hormonal contraceptives. This study aimed to describe how females with asthma perceived the effects of hormonal contraceptives on symptom severity, and to describe the association between asthma severity and current use of hormonal contraceptives.A questionnaire was sent to 891 females with asthma aged 20±30 yrs recruited from general practice registers in Sout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 18 publications
3
17
1
Order By: Relevance
“…However, during childbearing years, although a higher proportion of women suffer from premenstrual and menstrual worsening and severity of asthma, such exacerbation appears to occur at a time when estrogen is actually at its lowest circulating concentration and progesterone is at its highest circulating concentration (Chhabra, 2005; Farha et al, 2009; Vrieze et al, 2003). However, it is also important to note that some women with moderate asthma observe relief of their premenstrual asthma exacerbations if they use oral contraceptives that suppress large fluctuations in circulating hormones (Dratva et al, 2010; Forbes et al, 1999). These effects of exogenous estrogens negate a simple relationship between sex steroids and asthma in women.…”
Section: Sex Steroid Signaling In Disease Statesmentioning
confidence: 99%
“…However, during childbearing years, although a higher proportion of women suffer from premenstrual and menstrual worsening and severity of asthma, such exacerbation appears to occur at a time when estrogen is actually at its lowest circulating concentration and progesterone is at its highest circulating concentration (Chhabra, 2005; Farha et al, 2009; Vrieze et al, 2003). However, it is also important to note that some women with moderate asthma observe relief of their premenstrual asthma exacerbations if they use oral contraceptives that suppress large fluctuations in circulating hormones (Dratva et al, 2010; Forbes et al, 1999). These effects of exogenous estrogens negate a simple relationship between sex steroids and asthma in women.…”
Section: Sex Steroid Signaling In Disease Statesmentioning
confidence: 99%
“…1 Hormonal contraceptives showed no influence on asthma severity in women with relatively mild asthma. 2 Salam et al 3 showed that OCP was associated with more wheeze among subjects without asthma, and less wheeze among subjects with asthma. A modestly elevated asthma risk in past OCP users was observed in the Nurses Health Study.…”
mentioning
confidence: 98%
“…The role of exogenous sex hormones for asthma is still inconclusive, with studies reporting both improvement and worsening of symptoms as well as increased asthma incidence. [17][18][19][20][21][22][23] Most previous studies have been conducted in asthmatic outpatient populations. Even if symptoms of clinical importance might only be seen in a patient population, one should expect to find an impact of endogenous sex hormones also on the lung physiology of healthy individuals.…”
mentioning
confidence: 99%